Carbon Dots‐in‐EuAPO‐5 Zeolite: Triple‐Emission for Multilevel Luminescence Anti‐Counterfeiting. Issue 46 (11th October 2021) - Yu, Xiaowei; Liu, Kaikai; Zhang, Hongyue; Wang, Bolun; Ma, Wenyan; Li, Jiyang; Yu, Jihong
Abstract: Multilevel luminescence materials have aroused wide attention for their advanced anti‐counterfeiting abilities. However, various complicated stimuli factors involved in multilevel luminescence anti‐counterfeiting (MlLA) limit the practical applications of such materials. Herein, carbon dots (CDs) are in situ introduced into Eu‐substituted AlPO4 ‐5 zeolite (named CDs@EuAPO‐5) via a solvent‐free thermal crystallization method, which exhibits triple emissions including pink fluorescence mainly associated with Eu 3+ in the zeolite framework, blue fluorescence and green room temperature phosphorescence (RTP) associated with CDs. CDs are uniformly embedded in the EuAPO‐5 zeolite matrix. Such composite displays excellent photo‐, thermo‐, and solvent resistance, as well as long‐term storage‐stability. Moreover, the triple emissions of the composite only need two kinds of common excitation lights to trigger, without involving other complicated stimuli. A triple‐level luminescence anti‐counterfeiting (TlLA) label has been built, realizing facile, quick, and advanced luminescence anti‐counterfeiting that is hard to copy. Abstract : A feasible strategy for achieving multiple emissions in a single material is proposed by simultaneously introducing Eu 3+ and carbon dots into AlPO4 ‐5 zeolite. The triple emissions only need two simple excitation lights to trigger, without needing other complicated stimuli factors. As a proof of concept, a stable triple‐level luminescence anti‐counterfeiting (TlLA) label is built, realizing facile, quick, and advanced luminescence anti‐counterfeiting process.